Impact of Digitalization on Service Marketing in the Indian Banking Industry - Sharma, Pooja; Gupta, Dr. Sudipta Sen (Gyan Management Journal, 2023)
Globally, Indian banking is making the move to digitization. By the  late 1980s, the Indian banking industry had realized the need for  digitalization and that customer service needed to be considered as an  important aspect . Due to the adverse effects of several financial reforms  on India in the late 1980s, the banking industry saw a need to improve  customer service and computerize the recording of transactions and  knowledge accounting. Today, all banks make significant investments  in digital projects to keep a competitive advantage and offer their  clients the best service possible. After its launch, customers have  greatly profited from the convenience and time savings. All manual processes and activities have been replaced by digital  services. Although it has benefited customers and had a significant  impact on the Indian banking sector, there are still a number  of difficulties that arise. This paper will examine the effects of  digitalization on service marketing in the Indian banking sector and  how it has changed over time. This study’s main goal is to measure how  satisfied bank customers are with the online services they receive from  banks . This study makes use of the e – Servqual method to measure  quality of services provided to banking customers after digitalization  has taken place in the banking customers.
Keywords: Digitalization; Indian Banking Industry; Customer Service; Privacy; E – Servqual